Analisis Hukum terhadap Peran Pertamina sebagai State Trading Enterprise dalam Pelaksanaan Prinsip Non-Diskriminasi WTO: Studi Kasus Kebijakan Perdagangan Energi oleh Pertamina - Yovani Yolanda Putri Ginting (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The principle of non-discrimination constitutes a fundamental pillar of the international trading system governed by the World Trade Organization (WTO), aiming to ensure fair and open competition among its members. Nevertheless, the application of this principle faces challenges when states employ State Trading Enterprises (STEs) as policy instruments in strategic sectors, including energy. This study seeks to analyze the regulation of State Trading Enterprises within the WTO framework, particularly concerning the obligation to comply with the non-discrimination principle, and to examine the potential inconsistency of energy trade policies implemented by PT Pertamina (Persero) with this principle. This research adopts a normative legal research method, utilizing statutory and conceptual approaches through an examination of WTO provisions, especially Article XVII of the General Agreement on Tariffs and Trade 1994, along with international trade law doctrines. The findings indicate that the existence of State Trading Enterprises is recognized under the WTO system; however, their trading activities remain subject to the obligation to act in a non-discriminatory manner and based on commercial considerations. While state assignments to Pertamina are primarily intended to safeguard national energy security, such policies may give rise to potential implications for the WTO non-discrimination principle if not implemented transparently and objectively. Accordingly, a balance between national interests and international obligations is essential to ensure compliance with the multilateral trading regime.